Honokiol inhibits ultraviolet radiation-induced immunosuppression through inhibition of ultraviolet-induced inflammation and DNA hypermethylation in mouse skin - Ram Prasad (Nature Portfolio, 2017)
Abstract Ultraviolet (UV) radiation exposure induces immunosuppression, which contributes to the development of cutaneous malignancies. We investigated the effects of honokiol, a phytochemical found in plants of the genus Magnolia, on UVB-induced immunosuppression using contact hypersensitivity (CHS) as a model in C3H/HeN mice. Topical application of honokiol (0.5 and 1.0 mg/cm2 skin area) had a significant preventive effect on UVB-induced suppression of the CHS response. The inflammatory mediators, COX-2 and PGE2, played a key role in this effect, as indicated by honokiol inhibition of cyclooxygenase-2 (COX-2) expression and PGE2 production in the UVB-exposed skin. Honokiol application also inhibited UVB-induced DNA hypermethylation and its elevation of the levels of TET enzyme, which is responsible for DNA demethylation in UVB-exposed skin. This was consistent with the restoration of the CHS response in mice treated with the DNA demethylating agent, 5-aza-2′-deoxycytidine, after UVB exposure. There was no significant difference in the levels of inhibition of UVB-induced immunosuppression amongst mice that were treated topically with available anti-cancer drugs (imiquimod and 5-fluorouracil). This study is the first to show that honokiol has the ability to inhibit UVB-induced immunosuppression in preclinical model and, thus, has potential for use as a chemopreventive strategy for UVB radiation-induced malignancies.